Optimal Design of Piezoelectric Actuators for Shunt Damping Techniques - NEUBAUER, Marcus (Archives of Acoustics, 2014)
In vibration control with piezoceramics, a high coupling of the piezoelement with the structure is desired. A high coupling improves the damping performance of passive techniques like shunt damping. The coupling can be influenced by a the material properties of the piezoceramics, but also by the placement within the structure and the size of the transducer. Detailed knowledge about the vibration behaviour of the structure is required for this. This paper presents an in-depth analysis of the optimal shape of piezoelectric elements. General results for one-dimensional, but inhomogeneous strain distribution are provided. These results are applied to the case of a longitudinal transducer and a bending bimorph. It is obtained that for maximum coupling, only a certain fracture of the volume should be made of piezoelectric material.